Analisis Pengendalian Kualitas Produksi Menggunakan Peta Kendali U dan Diagram Kontrol Decision On Belief (DOB). - Nurul Rahmahani; Rito Goejantoro; Desi Yuniarti (EKSPONENSIAL, 2019)
Statistical quality control is a problem solving technique used to monitor, control, analyze, manage, and improve products. There are two kinds of control charts, namely the attribute control chart and the variable control chart. The Decision On Belief (DOB) control chart is an attribute control chart based on Bayes's Theorem. In this study, to determine the comparison of control chart U and the DOB control chart the degree of control sensitivity in identifying out of control data on the production quality control data banner of Lineza digital printing in Samarinda. Based on the result of the research, it is found that quality control using U control chart and DOB control diagram has not been statistically controlled because there is still data out of control and in better sensitivity level in detecting out of control data is a DOB control chart because this diagram detects 65% while the U control chart is only 15%.